The Necessity of Genetic Testing for Pediatric Steroid-Resistant Nephrotic Syndrome - Thom, Vu Thi; Pham, Dem Van; Dinh, Long Doan; Nguyen, Huong Quynh (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2018)
Primary nephrotic syndrome is one of the most common kidney disorders in children that could result in renal failure, even death. Many studies showed the correlation between gene polymorphisms and primary nephrotic syndrome. Currently, with rapid innovation of next generation sequencing, appropriate gene panels were recommended to patients with primary nephrotic syndrome to achieve the intended clinical benefits of treatment. NPHS1, NPHS2, WT1, LAMB2, PLCE1, LMX1B genes were known to be closely associated with congenital nephrotic syndrome, while NPHS1, NPHS2, WT1, LAMB2, PLCE1, TRPC6, ACTN4, ADCK4, COQ2, COQ6 were found related to pediatric primary nephrotic syndrome. For adult primary nephrotic syndrome, NPHS2, TRPC6, INF2, ACTN4, ADCK4 and WT1 were proved important. These diagnostic gene panels should be prescribed for primary nephrotic syndrome patients before immunotherapy treatment, renal biopsy, or kidney transplantation to achieve the highest treatment efficacy and to limit unexpected harmful side effects. Keywords Primary nephrotic syndrome, gene panel, immunotherapy, kidney biopsy, kidney transplantation References [1] Kang HG, Cheong HII. Nephrotic syndrome: what's new, what's hot. Korean J Pediatr. 2015; 58(8): 275-282. [2] Sang NN. Evaluation of treatment outcome using methylprednisolon and changing of immunoresponse before and after treatment of primary nephrotic syndrome in pediatrics patients. 1999; Department of pediatrics, Hanoi Medical University, Vietnam. [3] Zagury A, Oliveira AL, Montalvao JA, Novaes RH, Sa VM, Moraes CA, and Tavares S. Steroid-resistant idiopathic nephrotic syndrome in children: long-term follow-up and risk factors for end-stage renal disease. J Bras Nefrol. 2013; 35(3): 191-199. [4] Hugh MC, Wherlock M, Ognjanovic M, Kerecuk L, Hegde S, Feather S, Krischock L, Jones C, Sinha MD, Webb NJA, Martin C, Marks S, Koziell A, Welsh GI and Saleem MA. Simultaneous Sequencing of 24 Genes Associated with Steroid-Resistant Nephrotic Syndrome. Clin J Am Soc Nephrol. 2013; 8(4): 637-648. [5] Boute N, Roselli S, Benessy F, Lee H, Fuchshuber A, Dahan K, Gubler MC, Niaudet P, Antignac C. NPHS2, encoding the glomerular protein podocin, is mutated in autosomal recessive steroid resistant nephritic syndrome. Nature genetics. 2000; 24(4): 349-354. [6] Frishberg Y, Megged O, Shapira E, Feinstein S, Raas-Rothschild A. Mutations in NPHS2 encoding podocin are a prevalent cause of steroid resistant nephritic syndrome among Israeli-Arab children. J Am Soc Nephrol, 2002; 13(2): 400-405. [7] Berdeli A, Yavascan O, Serdaroqlu E, Bak M, Aksu N, Oner A, Anarat A, Donmez O, Yildiz N, Sever L, Tabel Y, Dusunsel R, Sonmez F, Cakar N. NPHS2 (podocin) mutations in Turkish children with idiopathic nephritic syndrome. Pediatr Nephrol. 2007; 22(12): 2031-2040. [8] Tory K, Menyhard DK, Woerner S, Nevo F, Gribouval O, Kerti A, Straner P, Arrondel C, Huynh Cong E, Tulassay T, Mollet G, Perczel A and Antignac C. Mutation-dependent recessive inheritance of NPHS2-associated steroid-resistant nephrotic syndrome. Nat Genet. 2014; 46(3): 299-304. [9] Jain V and Vasudevan P. Steroid-resistant nephrotic syndrome with mutations in NPHS2 (podocin): report from a three-generation family. Clin Kidney J. 2014; 7(3): 303-305. [10] 10. Otukesh H, Fereshtehnejad SM, Bakhshayesh M, Hashemi M, Hoseini R, Chalian M, Salami A, Mehdipor L, Rahiminia A. NPHS2 Mutations in Children with Steroid-Resistant Nephrotic syndrome. Iranian Journal of Kidney Diseases. 2009; 3(2): 99-102. [11] Jun L. Genetics of nephrotic syndrome in singapore pediatrics patients, in department of pediatrics. 2012; National University Singapore, Singapore. [12] Nguyen TKL, Pham VD, Nguyen TH, Pham TK, Nguyen TQH, Nguyen HH. Three novel mutations in NPHS1 gene in Vietnamese patients with congentital nephrotic syndrome. Caser Reports in Genetics. 2017; https://doi.org/10.1155/2017/2357282. [13] Giglio S, Provenzano A, Mazzinghi B, Becherucci F, Giunti L, Sansavini G, Ravaglia F, Roperto RM, Faretti S, Benetti E, Rotondi M, Murer L, Lazzeri E, Lasagni L, Materassi M, Romagnani P. Heterogenous genetic alterations in sporadic nephrotic syndrome associate with resistance to immunosuppression. J Am Soc Nephrol. 2015; 26:230-236. [14] Hinkes B, Wiggins RC, Gbadegesin R, Vlangos CN, Seelow D, Nurnberg G, Garg P, Verma R, Chaib H, Hoskins BE, Ashraf S, Becker C, Hennies HC, Goyal M, Wharram BL, Schachter AD, Mudumana S, Drummond I, Kerjaschki D, Waldherr R, Dietrich A, Ozaltin F, Bakkaloglu A, Cleper R, Basel-Vanagaite L, Pohl M, Griebel M, Tsygin AN, Soylu A, Muller D, Sorli CS, Bunney TD, Katan M, Liu J, Attanasio M, Otoole JF, Hasselbacher K, Mucha B, Otto EA, Airik R, Kispert A, Kelley GG, Smrcka AV, Gudermann T, Holzman LB, Nurnberg P, Hildebrandt F. Positional cloning uncovers mutations in PLCE1 responsible for a nephrotic syndrome variant that may be reversible. Nat Genet. 2006; 38: 1397-1405. [15] Gellermann J, Stefanidis CJ, Mitsioni A, Querfeld U. Succesful treatment of steroid resistant nephrotic syndrome associated with WT1 mutations. Pediatr Nephrol. 2010; 25: 1285-1289. [16] Ruf RG, Lichtenberg A, Karrle SM, Haas JP, Anacleto FE, Schultheiss M, Zalewski I, Imm A, Ruf EM, Mucha B, Bagga A, Neuhaus T, Fuchshuber A, Bakkaloglu A, Hildebrandt F. Patients with mutations in NPHS2 (podocin) do not response to standart steroid treatment of nephrotic syndrome. J Am Soc Nephrol. 2004 15: 722-732. [17] Faul C, Donnelly M, Merscher-Gomez S, Chang YH, Franz S, Delfgaauw J, Chang JM, Choi HY, Campbell KN, Kim K, Reiser J, Mundel P. The actin cytoskeleton of kidney podocytes is a direct target of the antiproteinuric effect of cyclosporin A. Nat Med. 2008; 14: 931-938. [18] Bierzynska A, Mc Karthy HJ, Soderquest K, Sen ES, Colby E, Ding WY, Nabhan MM, Kerecuk L, Hegde S, Hughes D, Marks S, Feather S, Jones C, Webb NJ, Ognjanovic M, Christian M, Gilbert RD, Sinha MD, Lord GM, Simpson M, Koziell AB, Welsh GI, Saleem MA. Genomic and clinical profiling of a national nephrotic syndrome cohort advocates a precision medicine approach to disease management. Kidney Int. 2017; 91:937-947. [19] Santin S, Tazon-Vega B, Silva I, Cobo MA, Gimenez I, Ruiz P, Garcia Maset R, Ballarin J, Torra R, Ars E. Clinical value of NPHS2 analysis in early and adult onset steroid resistant nephrotic syndrome. Clin J Am Soc Nephrol. 2011; 6: 344-354. [20] Weber S, Gribouval O, Esquivel EL, Moriniere V, Tete MJ, Legendre C, Niaudet P, Antignac C. NPHS2 mutation analysis shows genetic heterogeneity of steroid resistant nephrotic syndrome and low post transplant recurrence. Kidney Int. 2004; 66: 571-579. [21] Konigshausen E, Sellin L. Circulating permeability factors in primary focal segmental glomerulosclerosis: a review of proposed candidates. Biomed Res Int. 2016;3765608. [22] Benoit G, Machuca E, Antignac C. Hereditary nephrotic syndrome: a systematic approach for genetic testing and a review of associated podocyte gene mutations. Pediatr Nephrol. 2010; 25:1621-1632. [23] Preston R, Stuart HM, Lennon R. Genetic testing in steroid-resistant nephrotic syndrome: why, who, when and how? Pediatric Nephrology.2017; https://doi.org/10.1007/s00467-017-3838-6. [24] Trautmann A, Bodria M, Ozaltin F, Gheisari A, Melk A, Azocar M, Anarat A, Caliskan S, Emma F, Gellermann J, Oh J, Baskin E, Ksiazek J, Remizzi G, Erdogan O, Akman S, Dusek J, Davitaia T, Ozkaya O, Papachristou F, Firszt-Adamczyk A, Urasinski T, Testa S, Krmar RT, Hyla Klekot L, Pasini A, Ozcakar ZB, Sallay P, Cakar N, Galanti M, Terzic J, Aoun B, Caldas Afonso A, Szymanik Grzelak H, Lipska BS, Schnaidt S, Schefer F, Podonet Consortium. Spectrum of steroid resistant and congenital nephrotic syndrome in children: the podonet registry cohort. Clin J Am Soc Nephrol. 2015; 10: 592-600. [25] Lovric S, Ashraf S, Tan W, Hildebrandt F. Genetic testing in steroid resistant nephrotic syndrome: when and how? Nephrol Dial Transplant. 2016; 31:1802-1813. [26] Kaplan JM, Kim SH, North KN, Rennke H, Correia La, Tong HQ, Mathis BJ, Rodriguez-Perez JC, Allen PG, Beggs AH, Pollak MR. Mutations in ACTN4 encoding alpha actinin-4, cause familial focal segmental glomerulosclerosis. Nat Genet. 2000; 24: 251-256. [27] Ashraf S, Gee HY, Woerner S, Xie LX, Vega-Warner V, Lovric S, Fang H, Song X, Cattran DC, Avila-Casado C, Paterson AD, Nitschke P, Bole-Feysot C, Cochat P, Esteve-Rudd J, Haberberger B, Allen SJ, Zhou W, Airik R, Otto EA, Barua M, Al-Hamed MH, Kari JA, Evans J, Bierzynska A, Saleem Ma, Bockenhauer D, Kleta R, El Desoky S, Hacihamdioglu DO, Gok F, Waskburn J, Wiggins RC, Choi M, Lifton RP, Levy S, Han Z, Salviati L, Prokisch H, Williams DS, Pollak M, Clarke CF, Pei Y, Antignac C, Hildebrandt F. ADCK4 mutations promote steroid resistant nephrotic syndrome through CoQ10 bio-synthesis disruption. J Clin Invest. 2013; 123: 5179-5189. [28] Salviati L, Sacconi S, Murer L, Zacchello G, Franceschini L, Laverda AM, Basso G, Quinzii C, Angelini C, Hirano M, Naini AB, Navas P, DiMauro S, Montini G. Infantile encephalomyopathy and nephropathy with CoQ10 deficiency: a CoQ10 responsive condition. Neurology. 2005; 65: 606-608. [29] Heeringa SF, Chrrnin G, Chaki M, Zhou W, Sloan Ạ, Li Z, Xie LZ, Salviati L, Hurd TW, Vega-Warner V, Killen PD, Raphael Y, Ashraf S, Ovunc B, Schoeb DS, McLaughlin HM, Airik R, Vlangos CN, Gbadegesin R, Hinkes B, Saisawat P, Trevisson E, Doimo M, Casarin A, Pertegato V, Giorgi G, Prokisch H, Rotig A, Nurnberg G, Becker C, Wang S, Ozaltin F, Topaloglu R, Bakkaloglu A, Bakkaloglu SA, Muller D, Beissert A, Mir S, Berdeli A, Varpizen S, Zenker M, Matejas V, Santos-Ocana C, Navas P, Kussakabe T, Kispert A, Akman S, Soliman NA, Krick S, Mudel P, Reiser J, Nurnberg P, Clarke CF, Wiggins RC, Faul C, Hilebrandt F. CoQ6 mutations in human patients produce nephrotic syndrome with sensorineural deafness. J Clin Invest. 2011; 121: 2013-2024. [30] Kestila M, Lenkkeri U, Mannikko M, Lamerdin J, McCready P, Putaala H, Ruotsalainen V, Morita T, Nissinen M, Herva R, Kashtan CE, Peltonen L, Holmberg C, Olsen A, Tryggvason K. Postitionally cloned gene for a novel glomerular protein – nephrin- is mutated in congenital nephrotic syndrome. Mol Cell. 1998; 1: 575-582. [31] Winn MP, Conlon PJ, Lynn KL, Farrington MK, Creazzo T, Hawkins AF, Daskalakis N, Kwan SY, Ebersviller S, Burchette JL, Pericak-Vance Ma, Howell DN, Vance JM, Rosenberg PB. A mutation in the TRPC6 cation channel causes familial focal segmental glomerulosclerosis. Science. 2005; 308: 1801-1804 [32] Dreyer SD, Zhou G, Baldini A, Winterpacht A, Zabel B, Cole W, Johnson RL, Lee B. Mutations in LMX1B cause abnormal skeletal patterning and renal dysplasia in Nail Patella syndrome. Nat Genet. 1998; 19: 47-50. [33] Zenker M, Aigner T, Wendler O, Tralau T, Muntefering H, Fenski R, Pitz S, Schumacher V, Royer-Pokora B, Wuhl E, Cochat P, Bouvier R, Kraus C, Mark K, Madlon H, Dotsch J, Rascher W, Maruniak-Chudek I, Lennert T, Neumann LM, Reis A. Human laminin beta2 deficiency causes congenital nephrosis with mesangial sclerosis and distinct eye abnormalities. Hum Mol Genet. 2004; 13: 2625-2632. [34] Boyer O, Benoit G, Gribouval O, Nevo F, Tete MJ, Dantal J, Gilbert-Dussardier B, Touchard G, Karras A, Presne C, Grunfeld JP, Legendre C, Joly D, Rieu P, Mohsin N, Hannedouche T, Moal V, Gubler MC, Broutin I, Mollet G, Antignac C. Mutations in INF2 are a major cause of autosomal dominant focal segmental glomerulosclerosis. J Am Soc Nephrol. 2011; 22: 239-245.